Transfer Pricing and Growth Navigation Sales in a Dynamic Tax Environment in Indonesia - Sundari, Sri; Mallisa, Amalia Indah Pratama; Sapa', Angela Batara; Syamsuddin, Syamsuddin (Asian Journal of Applied Business and Management, 2024)
This study focuses on the relationship between transfer pricing and sales growth in a dynamic tax environment in Indonesia. Transfer pricing is an important issue for multinational companies in determining transaction prices between affiliated companies in various countries, including Indonesia, which has complex tax regulations. Transfer pricing practices are often used to optimize a company's tax burden by taking advantage of differences in tax rates between countries. However, the implementation of this strategy is not free from strict supervision by the Indonesian tax authorities, who continue to update policies and regulations to prevent tax avoidance. Along with the growth of the company's economy and sales, the challenges in navigating transfer pricing are increasing. Companies are faced with the need to maintain compliance with tax regulations while still focusing on sustainable sales growth. The dynamic tax environment in Indonesia requires companies to continue to adapt to changes in policies, which can affect their transfer pricing structure. Therefore, understanding the impact of ever-changing tax policies on transfer pricing strategies is an important key for companies that want to grow sustainably and avoid the risk of tax disputes with the authorities.